Other Games, Other Histories - Byrd, Jodi A. (ROMchip, 2019)
What could a history of game studies be from the perspective of a queer Chickasaw feminist scholar? Should this be a disciplining manifesto, a polemical call to arms for radical transformation, a survey of the existing scholarship that has thus far framed games ludologically as fun, as sportsmanship, as design, or as epic struggles for political power where the player rather ominously wins or dies? I’m a bit of an interloper as a recent arrival from Indigenous studies to video-game studies, a field that represents both the end of history and the ahistoricity of pop-culturally–oriented archives that are presentist at best, and at worst, complicit with an industry derived from settler militaristic technologies and platforms and compelled by niche markets to innovate faster and faster to saturate more and more households at the structural level of occupation. And then there is the problem of what the history of game studies has been: Greco-Roman, European, cis white male, heterosexual, orientalist, algorithmic, and code driven with the techno-optimism of Silicon Valley alongside Jane McGonigal’s fundamental belief that games have and will save the world once they unite the collective brain power of all the gamers and bend them to a single task—and if not all that, then peak 1980s geekery with a hint of liberal multiculturalism thrown in, if Ernest Cline’s Ready Player One is anything to go by. It is as if the history of game studies has only ever been an imperial read-only memory to be mined, played, and spatialized within the conscriptions of conquistador archives already known and yet to be discovered.
Number: 1
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Sovereign Words: Indigenous Art, Curation and Criticism - García-Antón, Katya (Office for Contemporary Art Norway, 2018)
Artists and cultural practitioners from Indigenous communities around the world are increasingly in the international spotlight. As museums and curators race to consider the planetary reach of their art collections and exhibitions, this publication draws upon the challenges faced today by cultural workers, Indigenous and non-Indigenous, to engage meaningfully and ethically with the histories, presents and futures of Indigenous cultural practices and world-views. Sixteen Indigenous voices convene to consider some of the most burning questions surrounding this field. How will novel methodologies of word/voice-crafting be constituted to empower the Indigenous discourses of the future? Is it sufficient to expand the Modernist art-historical canon through the politics of inclusion? Is this expansion a new form of colonisation, or does it foster the cosmopolitan thought that Indigenous communities have always inhabited? To whom does the much talked-of 'Indigenous Turn' belong? Does it represent a hegemonic project of introspection and revision in the face of today's ecocidal, genocidal and existential crises?"–Page 4 de la couverture. Autres auteurs/titres:edited by Katya García-Antón ; contributors, Daniel Browning, Kabita Chakma, Megan Cope, Santosh Kumar Das, Hannah Donnelly, Léuli Māzyār Luna'i Eshrāghi, David Garneau, Biung Ismahasan, Kimberley Moulton, Máret Ánne Sara, Venkat Raman Singh Shyam, Irene Snarby, Ánde Somby, Megan Tamati-Quennell, Prashanta Tripura, Sontosh Bikash Tripura.
Section: 287 pages : illustrations (principalement en couleur) ; 24 cm.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Re-Inventing Art Practices: Indigenous Women Artists Building Community through Art and Activism in Rural and Remote Manitoba - Nagam, Julie (University of Manitoba, 2006)
his thesis documents and explores community-based and socially engaged art by Indigenous women artists. Their artwork is impacting and strengthening communities in Manitoba. The Thesis explores the use of dialogical aesthetics in performance and socially-engaged art by Indigenous women artists in rural and remote areas of Manitoba, and relates these aesthetics to the concept of activism through their art and relationship to their community. The aim of this research and this paper is to document, support and expose the work of a small pocket of Indigenous women artists in Manitoba who are acting as activists or social change agents based on their artwork. I have arrived at this conclusion first by their personal testimonies, second, by their art being socially conscious and lastly, by their art practices entrenched in the framework of dialogical aesthetics, community-based and site-specific ideologies.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

(Re)Mapping the Colonized Body: The Creative Interventions of Rebecca Belmore in the Cityscape. - Nagam, Julie (American Indian Culture and Research Journal, 2011)
The cityscape holds the memories of indigenous bones and bodies that resurrect a deep sense of place that exists in the landscape of the city of Toronto. This deep sense of place is part of a connection to the land and stories of place. In this article, the author bridges the creative work of Anishinaabe artist Rebecca Belmore with the living histories of the indigenous bodies and bones that are buried beneath the ground of the city of Toronto and the city of Vancouver. She argues that Belmore's artwork is part of the living archive that performs cultural memory and employs telling as part of an embodied experience and a political act. Belmore's performance work creates, records, and stores indigenous stories of place. This article uses the ideas of cultural theorists Katherine McKittrick, Mishuana Goeman, and Matthew Sparke. Each of these people brings a different element to theories of the body and space. This article also uses feminist geographers Alison Blunt and Gillian Rose's work in women's colonial geographies to unpack the affects of the map in colonial spaces and the colonial gaze. (Contains 4 figures and 50 notes.)
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Becoming our future: global indigenous curatorial practice - Nagam, Julie; Tamati-Quennell, Megan; Lane, Carly (ARP Books, 2020)
"This book investigates international Indigenous methodologies in art curatorial practice from the geographic spaces of Canada, Aotearoa (New Zealand) and Australia. From a perspective of Indigenous peoples important place within society, this collection explores how Indigenous art and culture operate within and from a structural framework that is unique and is positioned outside of the non-Indigenous cultural milieu. Through a selection of contributions, Becoming Our Future articulates this perspective, defines Indigenous curatorial practice and celebrates Indigenous sovereignty within the three countries. It begins to explore the connections and historical moments that draw Indigenous curatorial practices together and the differences that set them apart. This knowledge is grounded in continuous international exchanges and draws on the breadth of work within the field. With contributions by Nigel Borell, Nici Cumpston, Freja Carmicheal, Karl Chitham, Franchesca Cubillo, Léuli Eshraghi, Reuben Friend, Jarita Greyeyes, Heather Igloliorte, Jaimie Isaac, Carly Lane, Michelle LaVallee, Cathy Mattes, Bruce McLean, Kimberley Moulton, Lisa Myers, Julie Nagam, Wanda Nanibush, Jolene Rickard, Megan Tamati-Quennell, and Daina Warren."– Provided by publisher.
Section: 240 pages : illustrations (chiefly color) ; 26 cm
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Knowledge Positions in Aotearoa and Turtle Island Art Museums - Eshraghi, Leuli; Ash-Milby, Kathleen; Nuku, Maia; Borell, Nigel (Artlink, 2020)
Art, performance, and spoken or now written text, all belong to the same register of cultural practice in the First Nations I am familiar with or belong to: ceremony. This ceremonial register takes place in a set of spaces created to enact cultural responsibilities to place, people and balance. Galleries and museums, as sites of cultural production and presentation, have the potential to nurture new ceremonies and new working methods.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Auto-histoires et représentations communautaires dans le cinéma des femmes autochtones - Bertrand, Karine (Canadian Journal of Film Studies, 2020)
In the last decade or so, cinema has revealed itself to be an ideal medium for the transfer and/or remediation of the spoken word as well as stories coming from oral tradition and Indigenous culture. Indeed, cinema is a place of expression which favours cyclical creativity and contributes to the decolonization of stereotyped images propagated by external voices that do not understand the subtleties of languages (real and symbolic) that are anchored in indigenous peoples’ cultural memory. By exploring indigenous cinema as practised by women of diverse nations, this piece demonstrates how cinema can induce the compression and dilation of time, to bring to the audience the fluidity of a story that has been reconfigured according to a new time and carried by spoken words that have chosen to either emancipate themselves from the image or to materialize themselves in it. Furthermore, this article illustrates how a new generation of Indigenous women use cinema to retrace and/or rewrite their personal narrative with the help of autobiographical or collective stories that travel back in time to fill in the blanks left by a fragile memory and to express their will to make peace with a difficult colonial past. Finally, the writings of Lee Maracle (I Am Woman, 1988) and Natasha Kanapé Fontaine (Manifeste Assi, 2014) are being brought forth to show how films such as Suckerfish (Lisa Jackson, 2004) Bithos (Elle-Máijá Tailfeathers, 2015) and Four Faces of the Moon (Amanda Strong, 2016) contribute to the individual and community healing of Indigenous peoples of Canada, through an aesthetic of reconciliation. The exploration of these works, therefore allows us to shed light on and better understand the roles/internal mechanisms of visual autobiographies in the larger context of reconciliation with individual and collective stories/memories.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Shelley Niro. Scotiabank Award. - Rice, Ryan; Nanibush, Wanda (Steidl Verlag, 2018)
Shelley Niro is widely known for her ability to explode myths, transgress boundaries and embody the ethos of her matriarchal culture in a wide variety of mediums including photography, installation, film and painting. Niro creates photographic series that emphasize the medium?s inherent capacity for narrative and representation. She pushes the limits of photography by incorporating Mohawk imagery, re-appropriating traditional stories such as Skywoman and The Peacemaker, and by focusing on contemporary subjects with wit, irony and campy humor. Niro marries portraiture, performance art and satire by having her subjects and herself perform for the camera in ways that gently invite audiences to rethink their beliefs and preconceptions about indigenous peoples and themselves. With compassion and deep insight, Niro opens up the fault lines and desires of gender, sexuality and culture to create images of freedom from the status quo in representation. Photography was a medium that helped subjugate indigenous peoples, but in Niro?s revolutionary hands it empowers
Section: 228 pages
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

George Littlechild: The Spirit Giggles Within - Littlechild, George (Heritage House Publishing Company Ltd, 2012)
George Littlechild: The Spirit Giggles Within is a stunning retrospective of a career that has spanned nearly four decades. Featuring more than 150 of the Plains Cree artist's mixed-media works, this sumptuous collection showcases the bold swaths of colour and subtle textures of Littlechild's work. Littlechild has never shied away from political or social themes. His paintings blaze with strong emotions ranging from anger to compassion, humour to spiritualism. Fully embracing his Plains Cree heritage, he combines traditional Cree elements like horses and transformative or iconic creatures with his own family and personal symbols in a unique approach. George Littlechild: The Spirit Giggles Within shows the evolution of an artist from his earliest works to the present day, including hints of future directions and themes. An insightful foreword by artist and curator Ryan Rice, a Mohawk from the Kahnawake First Nation in Quebec, and Littlechild's reflections on each piece build a broad understanding of Littlechild's work, his life and his views on the role of art within all cultures
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; _Nettoyé

Anthem: perspectives on home and native land - Rice, Ryan (Carleton University Art Gallery = Galerie d'art de l'Université Carleton, 2008)
Eight artists from across Canada create works identify varying forms of nationhood that either serve or detract from the concept of a national accord. Each artist explores the idea of ₃anthem₄ through a wide-angle lens, broadening the national discourse to include not only colonial histories, but also distinctive and multicultural liberties that take various forms: treaties, blood, languages, sexual orientation, faith, and oral traditions. The dynamic range of art works exhibited contribute to a more inclusive national narrative and expose and accept the diverse forms of nationalism that exist across the country.
Section: 61 pages : color illustrations ; 28 cm
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Kwah í:ken tsi Iroquois - Rice, Ryan (Ottawa Art Gallery = Galerie d'art d'Ottawa, 2008)
Catalogue d'exposition avec des textes de Ryan Rice, Françoise Charron, Emily Falvey et Hilda Nicholae.
Section: 132 pages : illustrations (chiefly color) ; 26 cm
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Hochelaga revisité = Hochelaga revisited - Rice, Ryan (MAI (Montréal, arts interculturels), 2009)
Catalogue d'exposition avec des textes de Ryan Rice; Jason Baerg; Lori Blondeau; Martin Loft; Cathy Mattes; Nadia Myre; Ariel Lightningchild Smith.
Section: 40 p. : ill. (certaines en coul.) ; 22 cm
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Presence and Absence Redux: Indian Art in the 1990s - Rice, Ryan (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
Les années 1990 sont une décennie cruciale pour l'avancement et le positionnement de l'art et de l'autonomie autochtones dans les récits dominants des états ayant subi la colonisation. Cet article reprend l'exposé des faits de cette période avec des détails fort nécessaires. Pensé comme une historiographie, il propose d'explorer chronologiquement comment les conservateurs et les artistes autochtones, et leurs alliés, ont répondu et réagi à des moments clés des mesures coloniales et les interventions qu'ellesontsuscitéesdu point de vue politique, artistique, muséologique et du commissariat d'expositions. À la lumière du 150e anniversaire de la Confédération canadienne, et quinze ans après la présentation de la communication originale au colloque, Mondialisation et postcolonialisme: Définitions de la culture visuelle v, du Musée d'art contemporain de Montréal, il reste urgent de faire une analyse critique des préoccupations contemporaines plus vastes, relatives à la mise en contexte et à la réconciliation de l'histoire de l'art autochtone sous-représentée.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Art of the Northwest Coast - Jonaitis, Aldona.. (University of Washington Press, 2006)
"Art of the Northwest Coast is a comprehensive survey of the Native arts of the Pacific Northwest Coast, spanning the region from Puget Sound to Alaska, and proceeding from prehistoric times to the present. Incorporating the region's social history with the observations of anthropologists, historians of art, and Native peoples, this rich, vibrant book reveals how a complex web of factors informed these groups' varied responses to the changes and challenges brought about by contact with Europeans."-
Section: 1 v. (XX-322 p.) : illustrations ; 25 cm
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Native Art of the Northwest Coast: A History of Changing Ideas - Townsend-Gault, Charlotte; Kramer, Jennifer (UBC Press, 2013)
This remarkable volume, many years in the making, records and scrutinizes definitions of Northwest Coast Native art and its boundaries. A work of critical historiography, it makes accessible for the first time in one place a broad selection of more than 250 years of writing on Northwest Coast "art." Organized thematically, its excerpted texts are from both published and unpublished sources, some not previously available in English. They cover such complex topics as the clash between oral and written knowledge, transcultural entanglement, the influence of surrealist thinking, and the long history of the deployment of Northwest Coast Native art for nationalist purposes. The selections are preceded by thought-provoking introductions that give historical context to the diverse intellectual traditions that have influenced, stimulated, and opposed each othe
Section: xxxvi, 1081 pages, 16 pages non numérotées en couleur : illustrations ; 26 cm
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Unsettling Native Art Histories on the Northwest Coast - Bunn-Marcuse, Kathryn B.; Jonaitis, Aldona (Bill Holm Center for the Study of Northwest Native Art, Burke Museum, in association with University of Washington Press, 2020)
"This edited collection focuses on "unsettling" Northwest Coast art studies, bringing forward voices that uphold Indigenous priorities, engage with past and ongoing effects of settler colonialism, and advocate for practices for more accountable scholarship. Featuring authors with a variety of perspectives, backgrounds, and methodologies, Unsettling Art Histories offers new insights for the field of Northwest Coast art studies. Key themes include discussions of cultural heritage protections and long-standing defenses of natural resources and territory; re-centering women and the critical role they play in transmitting cultural knowledge across generations through materials, techniques, and creations; reflecting on the decolonization work being undertaken in museums; and examining how artworks function beyond previous scholarly framings as living documents carrying information critical to today's inquiries. Re-examining previous scholarship and questioning current institutional practices by prioritizing information gathered in Native communities, the essays in this volume exemplify various methods of "unsettling" and demonstrate how new methods of research have reshaped scholarship and museum practices."
Section: 334 pages : illustrations (chiefly color) ; 27 cm.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Native Americans on Film: Conversations, Teaching, and Theory - Marubbio, M. Elise; Buffalohead, Eric L. (The University Press of Kentucky, 2012)
The film industry and mainstream popular culture are notorious for promoting stereotypical images of Native Americans: the noble and ignoble savage, the pronoun-challenged sidekick, the ruthless warrior, the female drudge, the princess, the sexualized maiden, the drunk, and others. Over the years, Indigenous filmmakers have both challenged these representations and moved past them, offering their own distinct forms of cinematic expression. Native Americans on Film draws inspiration from the Indigenous film movement, bringing filmmakers into an intertextual conversation with academic
Keywords: 1-Cinéma; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

La loi sur les Indiens revisitée = The Indian Act revisited - Sioui-Durand, Guy; Picard-Sioui, Louis-Karl (Musée huron-wendat, 2009)
Catalogue d'exposition
Section: 37 p. : ill. en coul. ; 28 cm
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Carl Beam: The Poetics of Being - Hill, Greg A. (National Gallery of Canada, 2010)
This major retrospective publication confirms Carl Beam (1943 - 2005) as one of North America's most important artists. Beam broke new ground throughout his career, notably as the first artist of Native Ancestry (Ojibwe) to have his work purchased by the National Gallery of Canada as Contemporary Art. Working in various mediums - photography, oil, acrylic, stone, cement, wood, ceramics and found objects - Beam's work continually explored the tensions between Western and Aboriginal relations. Featuring more than 50 of Beam's most remarkable works from his early career in the 1970s to the end of his production in the early 2000s, this richly illustrated monograph illuminates the artist's investigations into the metaphysical aspects of Western and Indigenous culture, while powerfully illustrating the wideranging physicality of his work. Source: Publisher
Section: 137 pages : illustrations (some color) ; 28 cm
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; _Nettoyé

Reservation X - McMaster, Gerald R. (Goose Lane, 1998)
Catalogue d'une exposition tenue à l'origine au "First People's Hall of the Canadian Museum of Civilization", prise en charge par Gerald McMaster. Publié avec le "Canadian Museum of Civilization
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Aboriginal Territories in Cyberspace - Lewis, Jason E.; Fragnito, Skawennati T. (Cultural Survival Quarterly., 2005)
Indigenous peoples are making their own spaces online, using art as the backdrop for cross-cultural dialogue. Cyberspace—the websites, chat rooms, bulletin boards, virtual environments, and games that make up the internet—offers Aboriginal communities an unprecedented opportunity to assert control over how we represent ourselves to each other and to non-Aboriginals. This article introduces the concept of Aboriginally determined territories in cyberspace and discusses how these can be defined, maintained, and expanded. We will do this within the Canadian context, though much of the discussion is pertinent to Aboriginal communities in other parts of the world. We draw on lessons learned from creating and curating CyberPowWow, an Aboriginally determined online gallery, to propose Aboriginal Territories in Cyberspace, a series of initiatives to expand Aboriginal presence online. These include expanding CyberPowWow into an ongoing community of new media artists addressing Aboriginal issues; developing Skins, a project in which elders work with youth to explore tribal stories through the use of online virtual environments; and laying the foundations for Within Reservations, which will function as a blueprint for equipping Aboriginals for full participation in the ongoing revolution in networked information technologies.
Place: Cambridge, Mass. OCLC: 109435875
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Afterlives of Indigenous archives: essays in honor of The Occom Circle - Schweitzer, Ivy; Henry, Gordon (Dartmouth College Press, 2019)
"Afterlives of Indigenous Archives offers a compelling critique of Western archives and their use in the development of “digital humanities.” The essays collected here present the work of an international and interdisciplinary group of indigenous scholars; researchers in the field of indigenous studies and early American studies; and librarians, curators, activists, and storytellers. The contributors examine various digital projects and outline their relevance to the lives and interests of tribal people and communities, along with the transformative power that access to online materials affords. The authors aim to empower native people to re-envision the Western archive as a site of community-based practices for cultural preservation, one that can offer indigenous perspectives and new technological applications for the imaginative reconstruction of the tribal past, the repatriation of the tribal memories, and a powerful vision for an indigenous future."
OCLC: 1080555941
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Indigenous Futurisms: Transcending Past/Present/Future - Herr, Chelsea; Well-Off-Man, Manuela; Fricke, Suzanne Newman (IAIA Museum of Contemporary Indian Arts, 2020)
Indigenous Futurisms: Transcending Past/Present/Future investigates a major trend in Contemporary Native Art–the rise of futuristic or science-fiction inspired Native American art. The essays and artworks present the future from a Native perspective and illustrate the use of Indigenous cosmology and science as part of tribal oral history and ways of life. Several of the artists use sci-fi related themes to emphasize the importance of Futurism in Native cultures, to pass on tribal oral history and to revive their Native language. However, Indigenous Futurism also offer a way to heal from the traumas of the past and present–the post-apocalyptic narratives depicted in some of the artworks are often reality for Indigenous communities worldwide.
OCLC: 1197536229
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

You Want to Do What with Doda’s Stories? Building a Community for the Skins Workshops on Aboriginal Storytelling in Digital Media - Lewis, Jason E.; Fragnito, Skawennati (Community-Based Multiliteracies & Digital Media Projects : Questioning Assumptions and Exploring Realities, 2014)
Aboriginal Territories in Cyberspace (AbTeC) is a research network of artists, academics and technologists centrally concerned with Indigenous representation in, and production of, digital media (AbTeC, 2008). AbTeC investigates and identifies ways for Indigenous peoples to tell our stories via networked technologies, and in so doing, strengthen our communities while proactively participating in shaping cyberspace. We are based at Concordia University, in Montreal, Quebec.
Section: xvi, 258 pages ; 23 cm.
Keywords: 1-Histoire de l'art; 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Aesthetics, Violence, and Indigeneity. - Rickard, Jolene (Public, 2016)
This essay considers the intersectionality between the field of art history focused on the subject category of Native American or Indigenous art and Indigenous Studies. Methodological gaps in the field of art history are discussed through the canonical genre of landscape art with a comparative reference to key exhibitions; Land Spirit Power: First Nations at the National Gallery of Canada, (1992), The West As America: Reinterpreting Images of the Frontier, 1820-1920, (1991), Submuloc Show/Columbus Wohs (1992), Our Land/Ourselves: Contemporary Native American Landscape (1991) and Picturing the Americas: Landscape Painting from Tierra del Fuego to the Artic (2015). The aestheticization of the colonization of the Americas as represented in the genre of landscape art is interrogated as a form of historical violence that needs to be decolonized within the field of art history.
OCLC: 1051992463
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Partial Recall - Benally, Suzanne (New Press, 1992)
In Partial Recall, twelve Native American artists and writers look deep into the images that have shaped our ideas of "Indianness," and explore the complex relationship of photography to identity. For this volume, edited and introduced by Lucy Lippard, each contributor has chosen one or two photographs as the point of departure for their original poetic, historical, political, or autobiographical essays. With an additional portfolio of more than sixty photographs drawn from around the country, Partial Recall is a unique and valuable anthology.
OCLC: 26767689
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Absorbing or Obscuring the Absence of a Critical Space in the Americas for Indigeneity: The Smithsonian's National Museum of the American Indian - Rickard, Jolene (Res: Anthropology and Aesthetics, 2007)
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; _Nettoyé

Visualizing Sovereignty in the Time of Biometric Sensors - Rickard, Jolene (South Atlantic Quarterly, 2011)
Multiple expressions of sovereignty beyond a narrow legal interpretation are discussed through the artwork of contemporary Iroquois artists, G. Peter Jemison (Seneca), Alan Michelson (Mohawk), Samuel Thomas (Cayuga), and Marie Watt (Seneca). Michelson's installation at the Massena homeland security border checkpoint between the United States, Canada, and the Mohawk Nation, titled The Third Bank of the River, draws on the Guswentah or Two Row Wampum underscoring the problematic yet ongoing assertion of Haudenosaunee sovereignty. A link is made between the work of these artists and the 2008 Courtney Hunt film, Frozen River, based on the cultural and political understanding of the Two Row Wampum. The Guswentah is discussed as a demonstration of sovereignty and is historicized through Cayuga chief Deskaheh's call for the recognition of Haudenosaunee sovereignty at the League of Nations in Geneva, in 1923, John Mohawk's 1978 Basic Call to Consciousness, and more recently, Taiaiake Alfred's 1999 Peace, Power, Righteousness. These artists demonstrate the critical role they play in the ongoing formation of sovereignty as a visual or aesthetic issue in conjunction with its historic legal positioning.
OCLC: 6965319862
Keywords: 1-Histoire de l'art; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Diversifying Sovereignty and the Reception of Indigenous Art - Rickard, Jolene (Art Journal, 2017)
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude de la réception; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Indigenous Feature Film Production in Canada: A National and International Perspective - Goulet, Danis; Swanson, Kerry (ImagineNATIVE Film + Media Arts Festival, 2014)
The goal of this research is to examine Aboriginal feature film production in Canada, specifically within the genre of drama. This report documents the rise of Indigenous cinema worldwide and examines Canada's public funding landscape including funding allocations to Aboriginal feature film production from Canada's public funders of film over a five-year period from 2007 to 2012. This report also examines the barriers to feature film production for Aboriginal content creators in Canada, and suggests areas of opportunity that can be targeted in order to boost production in this sector. Aboriginal film production is a relatively young sector, with scarce research existing on the industry. To address this gap in the available information on the sector, the researchers expanded the scope of the study beyond public funding agencies in Canada to include data from public funding agencies in Australia and New Zealand. Aboriginal feature film production in Canada is situated within a global Indigenous cinema context. Australia and New Zealand, in particular, are two pillars of global Indigenous film that offer a realistic point from which to compare Canada's progress. As a result, data from Australia and New Zealand are included in the study, as well as one model in the United States.
Keywords: 1-Cinéma; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Art for a New Understanding: Native Voices, 1950s to Now - Hopkins, Candice; Well-Off-Man, Manuela; Besaw, Mindy N.; Crystal Bridges Museum of American Art (University of Arkansas Press, 2018)
"Art for a New Understanding, an exhibition from Crystal Bridges Museum of American Art that opened in October 2018, seeks to radically expand and reposition the narrative of American art since 1950 by charting a history of the development of contemporary Indigenous art from the United States and Canada, beginning when artists moved from more regionally-based conversations and practices to national and international contemporary art contexts. This accompanying book documents and expands on the histories and themes of this exciting exhibition. This fully illustrated volume includes essays by art historians and historians and reflections by the artists included in the collection. Also included are key contemporary writings–from the 1950s onward–by artists, scholars, and critics, investigating the themes of transculturalism and pan-Indian identity, traditional practices conducted in radically new ways, displacement, forced migration, shadow histories, the role of personal mythologies as a means to reimagine the future, and much more. As both a survey of the development of Indigenous art from the 1950s to the present and a consideration of Native artists within contemporary art more broadly, Art for a New Understanding expands the definition of American art and sets the tone for future considerations of the subject. It is an essential publication for any institution or individual with an interest in contemporary Native American art, and an invaluable resource in ongoing scholarly considerations of the American contemporary art landscape at large."
Section: xiii, 205 pages : illustrations principalement en couleur, portraits ; 27 cm
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

The Land We Are: Artists & Writers Unsettle the Politics of Reconciliation - McCall, Sophie; L'Hirondelle Hill, Gabrielle (ARP Books, 2015)
The land we are' is a stunning collection of writing and art that interrogates the current era of reconciliation in Canada. Using visual, poetic, and theoretical language, the contributorsn approach reconciliation as a problematic narrative about Indigenous-settler relations, but also as a site where converseations about a just future must occur. The result of a four-year collaboration between artists and scholars engaged in resurgence and decolonization, 'The land we are' is a moving dialogue that blurs the boundaries between activism, research, and the arts
Section: viii, 225 pages : ment illustrations (principalement en couleur) ; 25 cm.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Àbadakone: feu continuel = continuous fire - Dickenson, Rachelle; Hill, Greg A.; Lalonde, Christine (Musée des beaux-arts du Canada, 2020)
Ce survol de l'art contemporain indigène, qui connut un succès retentissant dès son ouverture en novembre 2019, a été prolongé jusqu'au 4 octobre au Musée des beaux-arts du Canada. Àbadakone permet de découvrir des œuvres de plus de 70 artistes qui revendiquent leur appartenance à quelque 40 nations, ethnies et tribus de 16 pays, dont le Canada. Traitant des thèmes de la continuité, de l'activation et de l'interdépendance, Àbadakone explore la créativité, les préoccupations et la vitalité qui marquent l'art indigène de presque tous les continents. L'exposition est organisée par les conservateurs du Musée des beaux-arts du Canada Greg A. Hill, Christine Lalonde et Rachelle Dickenson, conseillés par les commissaires Candice Hopkins, Ariel Smith et Carla Taunton, ainsi que par une équipe d'experts du monde entier. .
Section: 271 pages : illustrations en couleur ; 25 cm
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Beat Nation: Art, Hip Hop and Aboriginal Culture - Ritter, Kathleen; Willard, Tania (Vancouver Art Gallery, 2012)
Catalgoue d'exposition
Section: 95 pages : illustrations en couleur
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Regards d'acier: portraits par des artistes autochtones. - Kunard, Andrea; Loft, Steve (Musée des beaux-arts du Canada, 2011)
Catalogue d'exposition avec plusieurs textes.
OCLC: 728495725
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Manifest Manners: Narratives on Postindian Survivance - Vizenor, Gerald Robert (Univ. of Nebraska Press, 2010)
Combines post-modern theory with the comic wisdom of the tribal trickster to explore the effects of nostalgic simulations of "Indian-ness".
OCLC: 837681052
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Indigena: Perspectives Autochtones Contemporaines - Martin, Lee-Ann; McMaster, Gerald (Musée canadien des civilisations, 1992)
Catlogue d'exposition avec plusieurs textes.
Section: 199 pages : illustrations (some color) ; 28 cm
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Inclusive and Exclusive Perceptions of Difference. Native and Euro Based Concepts of Time, History, Change - Doxtator, Deborah (Decentring the Renaissance: Canada and Europe in Multidisciplinary Perspective 1500–1700, 2001)
In 1558, confronted by the differences in the ways Native peoples and Europeans perceived and structured their respective societies, Renais- sance travel writer Andre Thevet asserted that the indigenous popula- tions of North America, unlike Europeans, had neither religion, civility, nor books, and lived like 'beasts without reason' (Thevet [1558] 1878, 134-6). In 1603, writing of the Native groups he encountered, Samuel de Champlain remarked that since each person 'prayed in his heart just as he liked,' they in effect had 'no law among them and do not know what it is to worship God and pray to Him, living as they do like brute beasts' (Champlain 1922-36, 6: 52). In contrast, Native groups, although not always conciliatory, nonetheless sought out ways to incorporate Europeans into existing political and ideological structures, inviting Champlain, Jesuit missionaries, and others to come to live with them and to participate in their way of life (Dickason 1992, 103, 107).A funda- mental element of Rotinonhsyonni1 diplomacy was the political neces- sity to achieve integrations so that, at least ideologically, Europeans and Iroquoians could perceive themselves to be brothers, one and the same people (Jesuit Relations [1610-1791] 1896-1901 [hereafter JR] 27: 253- 61). When Jacques Cartier encountered the Montagnais-Naskapi in 1534, he remarked on their ease of manners in their coming 'freely on board our vessels as if they had been Frenchmen' (Cartier 1924, 76).
Pages: 33-47
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Paix, pouvoir et droiture. Un manifeste autochtone - Alfred, Taiaiake (Éditions Hannenorak, 2014)
Paix, pouvoir et droiture : un manifeste autochtone, qui tire sa structure des chants rituels de la cérémonie de condoléances rotinohshonni, appelle toutes les Premières Nations à prêter attention aux messages des ancêtres afin de développer une philosophie visant à contrer l'assimilation. L'essai de Taiaiake Alfred est un véritable plaidoyer en faveur de droits et de l'autodétermination des peuples autochtones. Ce manifeste se veut avant-gardiste proposant des pistes de réflexion inédites ayant significativement participé à améliorer la compréhension des enjeux des Première Nations de l'Amérique du Nord.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; _Nettoyé

Kanata… appropriation ou effacement ? - Nepton Hotte, Caroline (esse arts + opinions, 2019)
Keywords: 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

L’appropriation culturelle et les peuples autochtones: entre protection du patrimoine et liberté de création. - Nepton-Hotte, Caroline; Jérôme, Laurent; Uzel, Jean-Philippe; Darsigny-Trépanier, Maude (GRIAAC, Groupe de recherche interdisciplinaire sur les affirmations autochtones contemporaines, 2019)
Le colloque « L’appropriation culturelle et les peuples autochtones : entre protection du patrimoine et liberté de création », organisé à l’UQAM en avril 2018, a suscité un dialogue fructueux à propos des multiples dimensions de l’appropriation culturelle. Réunissant des acteurs des milieux des arts et de la culture, du droit, de la politique, du tourisme et de la santé, ce colloque a permis de susciter des avenues de réflexion ainsi que différentes pistes d’action. Ce colloque, organisé par le Groupe de recherche interuniversitaire sur les affirmations autochtones contemporaines (GRIAAC-UQAM) en collaboration avec la Faculté des sciences humaines (FSH), la Société Recherches amérindiennes au Québec (SRAQ) et l’organisme Terres en vues, visait à réunir des experts et des praticiens des cultures et des sociétés autochtones (Premières Nations, Inuits et Métis), mais aussi des spécialistes des questions juridiques liées à la propriété intellectuelle, au droit d’auteur et aux droits collectifs, autour d’une question commune : comment respecter et protéger les traditions, les conceptions, les symboles, les savoirs, les patrimoines culturels matériels et immatériels autochtones, tout en continuant à favoriser la créativité et les échanges entre les cultures? À travers des présentations générales et des tables rondes réalisées sous forme d’ateliers, ce colloque visait non seulement à poser les termes de ces questions complexes, mais également à identifier des pistes concrètes d’actions pour que soient reconnues et respectées l’histoire, les lois et l’épanouissement tant des cultures autochtones que des autres cultures, et en particulier de la culture québécoise.
Section: 67 pages : illustrations (certaines en couleur) ; 28 cm
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Decolonize Me - Igloliorte, Heather; Loft, Steve; Croft, Brenda L. (Ottawa Art Gallery = Galerie d'art d'Ottawa, 2012)
Catalogue d'exposition avec des textes de Loft, Igloliorte et Croft. Galerie d'art d'Ottawa.
Section: 158 p. : ill. en coul. ; 24 cm.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

SakKijâjuk: Art and Craft from Nunatsiavut - Igloliorte, Heather; Broomfield, Jenna Joyce; Chaulk, Aimee; Lalonde, Christine; Pottle, Barry (Goose Lane Editions, 2017)
Nunatsiavut, the Inuit region of Canada that achieved self-government in 2005, produces art that is distinct within the world of Canadian and circumpolar Inuit art. The world's most southerly population of Inuit, the coastal people of Nunatsiavut have always lived both above and below the tree line, and Inuit artists and craftspeople from "Nunatsiavut have had access to a diverse range of Arctic and Subarctic flora and fauna, from which they have produced a stunningly diverse range of work. Artists from the territory have traditionally used stone and woods for carving; fur, hide, and sealskin for wearable art; and saltwater seagrass for basketry, as well as wool, metal, cloth, beads, and paper. In recent decades, they have produced work in a variety of contemporary art media, including painting, drawing, printmaking, photography, video, and ceramics, while also working with traditional materials in new and unexpected ways. SakKijâjuk: Art and Craft from Nunatsiavut is the first major publication on the art of the Labrador Inuit. Designed to accompany a major touring exhibition organized by The Rooms Provincial Art Gallery of St. John's, the book will feature more than 80 reproductions of work by 45 different artists, profiles of the featured artists, and a major essay on the art of Nunatsiavut by Heather Igloliorte. SakKijâjuk - "to be visible" in the Nunatsiavut dialect of Inuktitut - provides an opportunity for readers, collectors, art historians, and art aficionados from the South and the North will come into intimate contact with the distinctive, innovative, and always breathtaking work of the contemporary Inuit artists and craftspeople of Nunatsiavut
Section: 188 pages : illustrations (principalement en couleur) ; 32 cm
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Peau rouge, masques blancs: contre la politique coloniale de la reconnaissance - Coulthard, Glen Sean (Lux Editeur, 2018)
"Le paradigme hégélien de la reconnaissance, admirablement critiqué par Frantz Fanon dans l'œuvre phare à laquelle ce livre rend hommage, est aujourd'hui évoqué, sous sa forme libérale, dans les débats entourant l'autodétermination des peuples colonisés, notamment les peuples autochtones d'Amérique du Nord. Politologue et militant, membre de la Nation dénée du Nord-Ouest du Canada, l'auteur reprend ici la critique fanonienne et démontre en quoi cette reconnaissance ne fait que consolider la domination coloniale. Cet ouvrage de théorie politique engagée appelle à rebâtir et redéployer les pratiques culturelles des peuples colonisés sur la base de l'autoreconnaissance, seule voie vers une réelle décolonisation. Penseur marxiste, Coulthard sait que le marxisme ne peut s'appliquer tel quel à la lutte des Autochtones, mais il en souligne la contribution potentielle et signe ici un véritable traité de combat décolonial et anticapitaliste."
Section: 1 v. (359 p.) ; 19 cm
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; _Nettoyé

Pour une autohistoire amerindienne: essai sur les fondements d'une morale sociale - Sioui, Georges E (Presses de l'Université Laval, 1999)
Sioui has produced a work not only of metahistory but of moral reflections. He contrasts Euroamerican ethnocentrism and feelings of racial superiority with the Amerindian belief in the "Great Circle of Life" and shows that human beings must establish intellectual and emotional connections with the entire living world if they hope to achieve abundance, quality, and peace for all. Sioui is proud to be a Huron and an Amerindian and is fully aware of the injustices that the aboriginal people of North America have suffered - and continue to suffer - at the hands of Euroamericans. He is convinced that the greatness of Amerindians does not lie only in the past but that Native peoples will play an even more important role in the future by providing ideas essential to creating aviable way of life for North America and the world. While this is a polemical work, Sioui never descends to recrimination or vituperative condemnation, even when that might seem justified. Instead, he has given us a polemic that is written at the level of philosophy.
OCLC: 1132447000
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; _Nettoyé

D'horizons et d'estuaires: entre mémoires et créations autochtones - Larivée, Camille; Eshrāghi, Léuli (Éditions Somme toute, 2020)
"D'horizons et d'estuaires. Entre mémoires et créations autochtones est une collection d'essais réunissant les voix de 16 artistes, commissaires, historien·ne·s de l'art et travailleur·se·s culturel·le·s autochtones, tant francophones qu'anglophones, œuvrant dans les territoires que l'on nomme Québec. Faisant suite à des expositions, des performances, des résidences d'artistes et des discussions mises en place lors du Projet Tiohtià:ke (2017-2019) du Collectif des commissaires autochtones, ces textes honorent les relations et les affinités qui sont au cœur de ces pratiques en arts visuels. Quelle place occupe actuellement les créations visuelles autochtones dans la société québécoise? Comment les créateur·trice·s imaginent-iels le futur de leurs expressions culturelles? Par la diversité des points de vue et les enjeux soulevés par ces écrits, ce livre pose des questions cruciales sur l'avenir des arts autochtones et ouvre la porte à des dialogues longtemps attendus au Québec qui, nous l'espérons, permettront de créer de réels changements positifs. Il est maintenant temps de plonger dans ces imaginaires collectifs éblouissants et de nager dans les eaux ondulantes de ces mémoires résilientes. Le texte est accompagné de 28 photographies d'œuvres d'artistes autochtones."– Fourni par l'éditeur
Section: 148 pages : illustrations en couleur ; 21 cm
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Remix New Modernities in a Post-Indian World - Baker, Joe; McMaster, Gerald (Heard Museum/Natural Museum of American Indian, 2007)
Published in conjunction with the exhibition of the same name, on view at the Heard Museum in Phoenix, Arizona, from October 6, 2007, to April 27, 2008, and at the George Gustav Heye Center, National Museum of the American Indian, in New York, New York, from May 26 through September 30, 2008
OCLC: 845281405
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Jouer à l'Indien est une chose, être un Amérindien en est une autre - Sioui Durand, Guy (Recherches amérindiennes au Québec, 2003)
Ainsi en fut-il de la restitution en août 1999 par le Royal Ontario Museum des ossements des quelque cinq cents ancêtres wendats, illégalement extirpés en 1947 de la fosse commune d'Ossosané par les anthropologues du Musée, ceux-ci ayant retracé le site du dernier grand festin collectif en Huronie en 1636 (alors décrit par le père Brébeuf), ce qui a donné lieu à la résurgence d'une nouvelle grande fête des Morts, célébrée de de manière privée par les quatre nations de la diaspora wendatte, sous les offices d'un chamane iroquois traditionnaliste parlant encore le huron ; - la réactivation de ces types de créations comme manifestation authentiquement artistique autochtone et surtout comme mécanismes culturels de transmission aux jeunes générations. Bien que l'habitation nomade de la tente, sous la forme de tipi, fût celle qui a été la plus diffusée médiatiquement (entendre le cinéma hollywoodien et les séries de télévision des cow-boys et des Indiens des années cinquante et soixante pour identifier ceux qu'on appelle, depuis l'erreur d'identification du continent par Christophe Colomb, les « Indiens »), sa stylisation par une découpe moderne se démarquait des nombreuses reproductions kitsch. La performance An Indian Act Shooting the Indian Act (1997) de l'artiste Lawrence Paul Xuweluptun, dont rendait compte une projection vidéo accompagnant son exposition « Coulour Zone », en avril 2000, au Centre Saydie Bronfman de Montréal, et l'installation multimédia Resig/Nation (1999) de l'artiste saulteux et métis Edward Poitras au Lieu, Centre en art actuel, à Québec à l'hiver 2000, étaient radicales
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; _Nettoyé

Du grenier à la forêt : le musée de l’immatériel - Paré, Sylvie (Recherches amérindiennes au Québec, 2003)
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Nadia Myre, en[counter]s - Tougas, Colette; Couëlle, Marcia; Myre, Nadia (Éditions Art mûr, 2011)
Nadia Myre is a multidisciplinary artist whose work explores themes of language, culture, and memory, and who sources the culture of her Algonquin ancestors as a way of confronting contemporary realities. This monograph provides a comprehensive first look at this Montreal-based artist's remarkable career
Section: 93 pages : illustrations (principalement en couleur) ; 27 cm
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Numéro spécial : Cinémas et médias autochtones dans les Amériques : récits, communautés et souverainetés - Dudemaine, André; Marcoux, Gabrielle; St-Amand, Isabelle (Canadian Journal of Film Studies, 2020)
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Two-Spirit Resistance - Mcneil-Saymour, Jeffrey (Whose Land is it anyway? A Manual for Decolonization., 2017)
The publication of Whose Land Is It Anyway? A Manual for Decolonization is inspired by a 2016 speaking tour by Arthur Manuel, less than a year before his untimely passing in January 2017. The handbook provides a variety of Indigenous perspectives on the history of colonialism, current Indigenous activism and resistance, and outlines the path forward to reconciliation
Section: 79 pages : illustrations (some color) ; 29 cm
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice autochtone; _Nettoyé

Unsettled Landscapes - Dees, Janet; Hofmann, Irene; Hopkins, Candice; Sanromán, Lucia (SITE Santa Fe, 2014)
Published by SITE Santa Fe on occasion of the inaugural SITElines Biennial, 'Unsettled Landscapes'. Unsettled Landscapes was curated by Janet Dees, Irene Hofmann, Candice Hopkins, and Lucía Sanromán. The exhibition, featuring 47 artists from 14 countries, looks at the urgencies, political conditions and historical narratives that inform the work of contemporary artists across the Americas–from Nunavut to Tierra del Fuego. Through three themes–landscape, territory, and trade–this exhibition expresses the interconnections among representations of the land, movement across the land, and economies and resources derived from the land."–Résumé de l'éditeur
Section: 223 pages : illustrations (principalement en couleur) ; 24 cm.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Interpellations: Three Essays on Kent Monkman - Thériault, Michèle (Galerie Leonard & Bina Ellen art gallery, 2012)
Trois essais de Richard W. Hill, Jonathan D Katz et Todd B Porterfield.
Section: 118 p. : ill. en coul. ; 25 cm.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice LGBTQ+; 5-Créateur.rice autochtone; _Nettoyé

Indigenous and Decolonizing Studies in Education: Mapping the Long View - Tuhiwai Smith, Linda; Tuck, Eve; Yang, K. Wayne (Routledge, 2019)
Indigenous and decolonizing perspectives on education have long persisted alongside colonial models of education, yet too often have been subsumed within the fields of multiculturalism, critical race theory, and progressive education. Timely and compelling, Indigenous and Decolonizing Studies in Education features research, theory, and dynamic foundational readings for educators and educational researchers who are looking for possibilities beyond the limits of liberal democratic schooling. Featuring original chapters by authors at the forefront of theorizing, practice, research, and activism, this volume helps define and imagine the exciting interstices between Indigenous and decolonizing studies and education. Each chapter forwards Indigenous principles - such as Land as literacy and water as life - that are grounded in place-specific efforts of creating Indigenous universities and schools, community organizing and social movements, trans and Two Spirit practices, refusals of state policies, and land-based and water-based pedagogies.–publisher's description.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Arts of engagement: taking aesthetic action in and beyond the Truth and Reconciliation Commission of Canada - Martin, Keith; Robinson, Dylan (Wilfrid Laurier University Press, 2016)
It's about the role that music, film, visual art, and Indigenous cultural practices play in and beyond Canada's Truth and Reconciliation Commission on Indian Residential Schools. The essays question the ways in which components of the reconciliation, such as apology and witnessing, have social and political effects for residential-schools survivors, intergenerational survivors, and settler publics."– Provided by publisher
Section: viii, 374 pages : illustrations ; 23 cm
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Animalité. L’oeil amérindien - Sioui Durand, Guy (Inter, 2013)
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; _Nettoyé

Native Studies Keywords - Teves, Stephanie N.; Smith, Andrea; Raheja, Michelle H. (The University of Arizona Press, 2015)
"Native Studies Keywords explores selected concepts in Native studies and the words commonly used to describe them, words whose meanings have been insufficiently examined. This edited volume focuses on the following eight concepts : sovereignty, land, indigeneity, nation, blood, tradition, colonialism, and indigenous knowledge. Each section includes three or four essays and provides definitions, meanings, and significance to the concept, lending a historical, social, and political context. Take sovereignty, for example. The word has served as the battle cry for social justice in Indian Country. But what is the meaning of sovereignty? Native peoples with diverse political beliefs all might say they support sovereignty-without understanding fully the meaning and implications packed in the word. The field of Native studies is filled with many such words whose meanings are presumed, rather than articulated or debated. Consequently, the foundational terms within Native studies always have multiple and conflicting meanings. These terms carry the colonial baggage that has accrued from centuries of contested words. Native Studies Keywords is a genealogical project that looks at the history of words that claim to have no history. It is the first book to examine the foundational concepts of Native American studies, offering multiple perspectives and opening a critical new conversation"–Résumé du site web de l'éditeur
Section: xi, 356 pages : illustrations ; 23 cm.
Keywords: 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Baliser le territoire: a stake in the ground : Manifestation d'art contemporain autochtone - Myre, Nadia (Les Éditions Art Mûr, 2012)
Catalogue d'exposition. Du 14 janvier au 25 février 2012 à Art Mûr (Montréal. Titre : Baliser le territoire : Manifestation d’art contemporain autochtone / A Stake in the Ground: Contemporary Native Art Manifestation. Commissaire : Nadia Myre Sonny Assu, Jason Baerg, Carl Beam, Rebecca Belmore, Kevin Lee Burton, Hannah Claus, Bonnie Devine, Raymond Dupuis, Edgar Heap of Birds, Vanessa Dion Fletcher, Nicholas Galanin, Greg Hill, Robert Houle, Maria Hupfield, Rita Letendre, Glenna Matoush, Alan Michelson, Nadia Myre, Marianne Nicolson, Michael Patten, Arthur Renwick, Sonia Robertson, Greg Staats, Tania Willard, Will Wils
Section: 30 pages : illustrations principalement en couleur ; 21 cm
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Le ré-ensauvagement par l’art: Le vieil Indien, les pommes rouges et les Chasseurs-Chamanes-Guerriers - Sioui Durand, Guy (Captures, 2018)
L’article part de la notion wendat d’ohtehra’ pour développer une approche de l’art contemporain autochtone comme processus de « ré-ensauvagement » à l’œuvre, entre autres, chez les artistes Kent Monkman (Cri-Irlandais) et Caroline Monnet (Anishinaabe-Française). L’auteur, en s’appuyant sur les théoriciens Deborah Doxtator (Kanien’kehá:ka), Georges Emery Sioui (Wendat) et Taiaiake Alfred (Kanien’kehá:ka) propose également une analyse de l’autochtonie en Amérique du Nord comme un fait glocal d’Américité.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Sakahàn: art indigène international - Hill, Greg A.; Lalonde, Christine.; Hopkins, Candice (Musée des beaux-arts du Canada, 2013)
Sakahàn' celebrates a growing international commitment to the collection, study and exhibition of indigenous art. Featuring more than 75 artists from around the world, this remarkable project places indigenous art squarely at the centre of contemporary art produced today.
Section: 285 p. : ill. en coul. ; 25 cm.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé

Reservation Reelism: Redfacing, Visual Sovereignty, and Representations of Native Americans in Film. - Raheja, Michelle H. (University of Nebraska Press, 2011)
In this deeply engaging account, Michelle H. Raheja offers the first book-length study of the Indigenous actors, directors, and spectators who helped shape Hollywood's representation of Indigenous peoples. Since the era of silent films, Hollywood movies and visual culture generally have provided the primary representational field on which Indigenous images have been displayed to non-Native audiences. These films have been highly influential in shaping perceptions of Indigenous peoples as, for example, a dying race or as inherently unable or unwilling to adapt to change. However, films with Ind
Keywords: 1-Cinéma; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé; _À vérifier-Cinéma

Indigenous Art: New Media and the Digital - Igloliorte, Heather; Nagam, Julie; Taunton, Carla (Public, 2016)
Indigenous Art New Media and the Digital convenes leading scholars, curators, and artists from the Indigenous territories in Canada, the United States of America, Australia, and Aotearoa (New Zealand). It brings forth urgent conversations about resistance to colonial modernism, and highlights the historic and ongoing use of technology by Indigenous communities and artists as vehicles of resilience and cultural continuity. This issue ignites productive dialogue around the definitions of new and digital media art and practice-based work within the framework of Indigenous art and theory
Section: 215 pages : illustrations (principalement en couleur) ; 24 cm.
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Call it a Vision Quest : Machinima in a First Nations context - Lapensée, Elizabeth; Lewis, Jason E. (Understanding Machinima Essays on Filmmaking in Virtual Worlds, 2013)
Article sur les machinimas de l'artiste Skawennati (Kanien'kehá:ka) et du travail du laboratoire d'ABTEC (Aboriginal Territories on cyberspace) à l'Université Concordia.
Keywords: 1-Histoire de l'art; 2-Recherche-création; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé; _À vérifier-Jeu vidéo

Decolonization is not a Metaphor - Tuck, Eve; K. Wayne Yang (Journal Publishing Services, 2012)
Our goal in this article is to remind readers what is unsettling about decolonization. Decolonization brings about the repatriation of Indigenous land and life; it is not a metaphor for other things we want to do to improve our societies and schools. The easy adoption of decolonizing discourse by educational advocacy and scholarship, evidenced by the increasing number of calls to “decolonize our schools,” or use “decolonizing methods,” or, “decolonize student thinking”, turns decolonization into a metaphor. As important as their goals may be, social justice, critical methodologies, or approaches that decenter settler perspectives have objectives that may be incommensurable with decolonization. Because settler colonialism is built upon an entangled triad structure of settler-native-slave, the decolonial desires of white, non-white, immigrant, postcolonial, and oppressed people, can similarly be entangled in resettlement, reoccupation, and reinhabitation that actually further settler colonialism. The metaphorization of decolonization makes possible a set of evasions, or “settler moves to innocence”, that problematically attempt to reconcile settler guilt and complicity, and rescue settler futurity. In this article, we analyze multiple settler moves towards innocence in order to forward “an ethic of incommensurability” that recognizes what is distinct and what is sovereign for project(s) of decolonization in relation to human and civil rights based social justice projects. We also point to unsettling themes within transnational/Third World decolonizations, abolition, and critical space-place pedagogies, which challenge the coalescence of social justice endeavors, making room for more meaningful potential alliances
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

First Person Plural: Aboriginal Storytelling and the Ethics of Collaborative Authorship - McCall, Sophie (UBC Press, 2011)
Told-to narratives, or collaboratively produced texts by Aboriginal storytellers and (usually) non-Aboriginal writers, often confound traditional literary understandings of voice and authorship. In this innovative exploration, these unique narratives are not romanticized as unmediated translations of oral documents, nor are they dismissed as corruptions of original works. Rather, the approach emphasizes the interpenetration of authorship and collaboration. Discussing a wide range of told-to narratives, including ethnography, recorded (auto)biography, testimonial life narrative, documentary, myth, legend, and song, Sophie McCall explores the multifaceted implications of the choices that editors, translators, narrators, and filmmakers make as they channel these narratives into new forms. Focused on the 1990s, when debates over voice and representation were particularly explosive, this comprehensive study examines collaboratively produced texts in conjunction with key political events that have shaped the struggle for Aboriginal rights in Canada. Emphasizing the scope rather than the limits of the told-to narrative, McCall considers how Aboriginal voices have been represented in a range of forums such as public inquiries, commissioners’ reports, and land claims court cases. A captivating inquiry, First Person Plural offers a vital, interdisciplinary discussion of how told-to narratives contribute to larger debates about Indigenous voice and literary and political sovereignty. This innovative, interdisciplinary study will be of interest to students and scholars of Indigenous studies, textualized oral narrative, literary studies, and Canadian cultural studies
Section: ix, 254 p. ; 24 cm
Keywords: 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Transference, Tradition, Technology: Native New Media Exploring Visual & Digital Culture - Townsend, Melanie A.; Hopkins, Candice (Walter Phillips Gallery Editions, 2005)
Transference, Tradition, Technology explores Canadian Aboriginal new media and references the work of artists within a political, cultural and aesthetic milieu. The book constructs a Native art history relating to these disciplines, one that is grounded in the philosophical and cosmological foundations of Aboriginal concepts of community and identity within the rigour of contemporary arts discourse. Approachable in nature but scholarly in content, this book is the first of its kind. A text book for students and teachers of Canadian Aboriginal history and visual and media art, and a source for writers, scholars and historians, Transference, Tradition, Technology is co-produced with the Art Gallery of Hamilton, Hamilton; and Indigenous Media Arts Group, Vancouver.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

“I Want to Call Their Names in Resistance”: Writing Aboriginal Women into Canadian Art History. - Farrell Racette, Sherry (Rethinking Professionalism: Essays on Women and Art in Canada, 1850-1970, 2012)
As bell hooks points out in “Aesthetic Inheritances: History Worked by Hand,” writing an inclusive art history is no easy task. Until very recently, Aboriginal women have been written out of Canadian art history, or rather art history has been written around us. How do we write ourselves in? It falls far beyond simple insertion; the erasures are far too deep. Insertion presumes a simple forgetfulness, an oversight, a neglecting of the obvious. Insertion assumes a presence. It implies a shared mode of history, a common belonging to a collective archive, and an agreed-upon understanding of what it means to be an artist. Beyond the important considerations of race, gender, culture, and social class, our distinct legal status in Canada must be acknowledged. This was particularly true for women artists working between 1880 and 1970. For much of the time period under consideration, First Nations communities lived under a profoundly restrictive regime of colonial power. Relationships between First Nations people and the Canadian state have been defined by the Indian Act, a piece of legislation enacted in 1876 and surviving, through many amendments and revisions, until the present time.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Returning Fire, Pointing the Canon: Aboriginal Photography as Resistance - Farrell Racette, Sherry (The Cultural Work of Photography in Canada, 2011)
Résumé livre : The Cultural Work of Photography in Canada is an in-depth study on the use of photographic imagery in Canada from the late nineteenth century to the present. This volume of fourteen essays provides a thought-provoking discussion of the role photography has played in representing Canadian identities. In essays that draw on a diversity of photographic forms, from the snapshot and advertising image to works of photographic art, contributors present a variety of critical approaches to photography studies, examining themes ranging from photography's part in the formation of the geographic imaginary to Aboriginal self-identity and notions of citizenship. The volume explores the work of photographs as tools of self and collective expression while rejecting any claim to a definitive, singular t... Source: Publisher
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

‘Enclosing Some Snapshots’: James Patrick Brady, Photography, and Political Activism - Farrell Racette, Sherry (History of Photography, 2018)
James Brady was a mid twentieth-century Indigenous political organiser, trapper, prospector, writer, and intellectual. He was also a prolific photographer. This article considers the significance and aesthetics of Brady’s photographic archive through the lens of Indigenous visual sovereignty. Brady was Métis - one of Canada’s three recognised Indigenous peoples along with First Nations and Inuit. The Métis engaged in two conflicts with the Canadian state and negotiated the entry of a province into confederation. For a significant period of history, they lived outside Canadian infrastructures, whether the system of First Nations’ reserves created in the post-treaty era or Euro-Canadian settlements. Particularly vulnerable to land loss and displacement, the Métis were in desperate condition when Brady first began travelling with his camera. Brady’s photographs document the political rebirth of Métis people and the resilience and persistence of Métis communities in northern Alberta and Saskatchewan. They bear photographic witness to the lived experience of sovereignty rooted to place and continue to resonate with his subjects and their descendants
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

Art in our Lives native Women Artists in Dialogue - Chavez Lamar, Cynthia; Farrell Racette, Sherry; Evans, Lara (School for Advanced Research Press, 2010)
The culmination of three seminars at SAR's Indian Arts Research Center (IARC) that brought together Native women artists to discuss the balancing of their art practice with the myriad roles, responsibilities, and commitments they have. The artworks were diverse in media and content and are featured in the plates section of this volume, along with the artist statements that accompanied the pieces in the exhibit. The chapters reflect some of the seminars emerging themes: gender, home/crossing, and art as healing/art as struggle
Section: 1 v. (x-142 p.) : ill. en coul. ; 26 cm
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Coded Territories: Tracing Indigenous Pathways in New Media Art - Loft, Steve; Swanson, Kerry (University of Calgary Press, 2014)
This collection of essays provides a historical and contemporary context for Indigenous new media arts practice in Canada. The writers are established artists, scholars, and curators who cover thematic concepts and underlying approaches to new media from a distinctly Indigenous perspective. Through discourse and narrative analysis, the writers discuss a number of topics ranging from how Indigenous worldviews inform unique approaches to new media arts practice to their own work and specific contemporary works. Contributors include: Archer Pechawis, Jackson 2Bears, Jason Edward Lewis, Steven Foster, Candice Hopkins, and Cheryl L'Hirondelle.
Section: xvii, 195 pages : illustrations en couleur ; 22 cm
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

Indigenous Methodologies: Characteristics, Conversations, and Contexts - Kovach, Margaret (University of Toronto Press, 2009)
"An innovative and important contribution to Indigenous research approaches, this revised second edition provides a framework for conducting Indigenous methodologies, serving as an entry point to learn more broadly about Indigenous research."–
OCLC: 1223012487
Keywords: 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé